Two-degree-of-freedom compensator design for disturbance attenuation problem via higher order sinusoidal input describing functions theory - Erol, Bilal; Oz, Muhammed Ali; Ucun, Levent (SAGE PUBLICATIONS LTD, 2021)
In order to deal with disturbance attenuation problem in the presence of norm bounded uncertainties, different techniques involving H2/H infinity and linear quadratic regulator (LQR) designs exist in literature. The major drawbacks of these approaches may be classified as obtaining controllers with high order terms and too much computational load during the controller design. Hence, two-degree-of freedeom (2-DOF) controller design is taken into consideration in this study in order to avoid some of these drawbacks in the controller design and implementation process for disturbance attenuation problem. Here, the procedure for the design of 2-DOF structure is divided into two parts: designing H infinity controller to stabilize the closed loop system and implementing a higher order sinusoidal input describing functions (HOSIDF)-based compensator as a secondary controller in order to increase the disturbance attenuation performance of the overall closed loop system where the norm bounded uncertainties already exist. Thanks to the Lur'e type system definition that is also used in the design process of HOSIDF compensator, the research also proves that the proposed 2-DOF design structure is suitable to be implemented into the systems involving nonlinearities such as actuator saturation.
Keywords: Describing functions; 2-DOF controller; disturbance attenuation problem; Script capital H-infinity control theory; active suspension system; INFINITY CONTROLLER-DESIGN; FRICTION COMPENSATION; SYSTEMS; Automation & Control Systems; Instruments & Instrumentation